2019
DOI: 10.1002/mrm.27783
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective correction of motion‐affected MR images using deep learning frameworks

Abstract: Purpose Motion is 1 extrinsic source for imaging artifacts in MRI that can strongly deteriorate image quality and, thus, impair diagnostic accuracy. In addition to involuntary physiological motion such as respiration and cardiac motion, intended and accidental patient movements can occur. Any impairment by motion artifacts can reduce the reliability and precision of the diagnosis and a motion‐free reacquisition can become time‐ and cost‐intensive. Numerous motion correction strategies have been proposed to red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
97
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(98 citation statements)
references
References 31 publications
0
97
0
1
Order By: Relevance
“…Further reductions in scan time may be achievable by removing the need for respiratory navigation, however this would result in blurring and loss of resolution in the acquired images due to breathing motion. Machine learning algorithms have recently shown the potential to recover high resolution images from this motion corrupted data [ 25 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further reductions in scan time may be achievable by removing the need for respiratory navigation, however this would result in blurring and loss of resolution in the acquired images due to breathing motion. Machine learning algorithms have recently shown the potential to recover high resolution images from this motion corrupted data [ 25 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, methods that better correlate with human ratings are preferred. Considering typical usage of NR methods, limited to 2D images, NORMIQA can be applied to select best performing denoising techniques, approaches for correcting artifacts, or image reconstruction solutions . Also, the method can be used to support subjective tests with human observers since such an assessment is often unrepeatable.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we sought to investigate the use of deep neural networks (DNNs) for respiratory motion compensation in MRI to alleviate some of the aforementioned problems. DNNs, particularly convolutional DNNs, have presented new possibilities for tackling a wide range of inverse problems including image in-painting, super resolution, [20][21][22][23] denoising and deblurring [24][25][26][27][28][29][30] in an efficient manner. The main advantage of a DNN over classical data-processing approaches is that it learns the effective features and priors in a data-driven fashion.…”
Section: Introductionmentioning
confidence: 99%
“…To date, few studies have implemented DNNs for motion compensation. [30][31][32][33][34] Recent studies have shown that DNN can correct rigid-motion artifacts in brain imaging. 31,32,35 They mainly trained convolutional neural networks (CNNs) with pixel-wise objective functions in a supervised manner.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation